Tailoring silk fibroin hydrophilicity and physicochemical properties using sugar alcohols for medical device coatings - Supranee Kaewpirom; Sarayoot Piboonnithikasem; Pongsathorn Sroisroemsap; Sittichai Uttoom; Siridech Boonsang (My University, 2024)
Abstract This study explores the modification of silk fibroin films for hydrophilic coating applications using various sugar alcohols. Films, prepared via solvent casting, incorporated glycerol, sorbitol, and maltitol, revealing distinctive transparency and UV absorption characteristics based on sugar alcohol chemical structures. X-ray diffraction confirmed a silk I to silk II transition influenced by sugar alcohols. Glycerol proved most effective in enhancing the β-sheet structure. The study also elucidated a conformational shift towards a β-sheet structure induced by sugar alcohols. Silk fibroin–sugar alcohol blind docking and sugar alcohol-sugar alcohol blind docking investigations were conducted utilizing the HDOCK Server. The computer simulation unveiled the significance of size and hydrogen bonding characteristics inherent in sugar alcohols, emphasizing their pivotal role in influencing interactions within silk fibroin matrices. Hydrophilicity of ozonized silicone surfaces improved through successful coating with silk fibroin films, particularly glycerol-containing ones, resulting in reduced contact angles. Strong adhesion between silk fibroin films and ozonized silicone surfaces was evident, indicating robust hydrogen bonding interactions. This comprehensive research provides crucial insights into sugar alcohols’ potential to modify silk fibroin film crystalline structures, offering valuable guidance for optimizing their design and functionality, especially in silicone coating applications.
Keywords: Fibroin; Sugar alcohol; Silk-based biomaterials and applications